2020
DOI: 10.1177/0253717620958162
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress, Coping and Perceived Social Support Among Partners of Women with Postpartum Onset Severe Mental Illness (SMI) Admitted to a Mother–Baby Unit

Abstract: Background: The presence of a severe mental illness in the mother during the postpartum period may impact the whole family and specifically have an effect on the health of the spouse. The current study aimed to assess psychological distress, coping, and perceived social support of spouses of women with postpartum onset severe mental illness. Methodology: A cross-sectional descriptive research design was used, and 30 spouses of the women admitted to the mother–baby unit (MBU) for psychiatric inpatient care were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Davies et al identified the need to address maternal depressive symptoms as distinct issues considering their differential effects on parenting behavior [ 9 ]. Other studies have also shown that the incidence of postpartum depression in women can cause depression and anxiety in their husbands [ 10 , 11 ]. Postpartum psychological problems also have heavy economic costs for healthcare systems.…”
Section: Introductionmentioning
confidence: 99%
“…Davies et al identified the need to address maternal depressive symptoms as distinct issues considering their differential effects on parenting behavior [ 9 ]. Other studies have also shown that the incidence of postpartum depression in women can cause depression and anxiety in their husbands [ 10 , 11 ]. Postpartum psychological problems also have heavy economic costs for healthcare systems.…”
Section: Introductionmentioning
confidence: 99%